The world recognises : e-farmer@acp-farmers.net* - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
With the Internet being a way to market your goods and information, as well as to correspond or conduct research, the way you look becomes more important. Each user has a unique address; most people restrict it to their name (to the left of @),...